Heterologous expression, purification and biochemical characterization of a glutamate racemase (MurI) from Streptococcus mutans UA159 - Xiangzhu Wang; Chanchan Chen; Ting Shen; Jiangying Zhang (PeerJ, 2019)
Background Glutamate racemase (MurI) is a cofactor-independent enzyme that is essential to the bacterial peptidoglycan biosynthesis pathway and has therefore been considered an attractive target for the development of antimicrobial drugs. While in our previous study the essentiality of the murI gene was shown in Streptococcus mutans, the primary aetiologic agent of human dental caries, studies on S. mutans MurI have not yet provided definitive results. This study aimed to produce and characterize the biochemical properties of the MurI from the S. mutans UA159 genome. Methods Structure characterization prediction and multiple sequence alignment were performed by bioinformatic analysis. Recombinant His6-tagged S. mutans MurI was overexpressed in the expression vector pColdII and further purified using a Ni2+ affinity chromatography method. Protein solubility, purity and aggregation state were analyzed by SDS–PAGE, Western blotting, native PAGE and SEC-HPLC. Kinetic parameters were assessed by a circular dichroism (CD) assay. Kinetic constants were calculated based on the curve fit for the Michaelis–Menten equation. The effects of temperature and pH on enzymatic activity were determined by a series of coupled enzyme reaction mixtures. Results The glutamate racemase gene from S. mutans UA159 was amplified by PCR, cloned and expressed in Escherichia coli BL21 (DE3). The 264-amino-acid protein, as a mixture of dimeric and monomeric enzymes, was purified to electrophoretic homogeneity. In the CD assay, S. mutans MurI displayed unique kinetic parameters (Km, d-Glu→l-Glu = 0.3631 ± 0.3205 mM, Vmax, d-Glu→l-Glu = 0.1963 ± 0.0361 mM min−1, kcat, d-Glu→l-Glu = 0.0306 ± 0.0065 s−1, kcat/Km, d-Glu→l-Glu = 0.0844 ± 0.0128 s−1 mM−1, with d-glutamate as substrate; Km, l-Glu→d-Glu = 0.8077 ± 0.5081 mM, Vmax, l-Glu→d-Glu = 0.2421 ± 0.0418 mM min−1, kcat, l-Glu→d-Glu = 0.0378 ± 0.0056 s−1, kcat/Km, l-Glu→d-Glu = 0.0468 ± 0.0176 s−1 mM−1, with l-glutamate as substrate). S. mutans MurI possessed an assay temperature optimum of 37.5 °C and its optimum pH was 8.0. Conclusion The findings of this study provide insight into the structure and biochemical traits of the glutamate racemase in S. mutans and supply a conceivable guideline for employing glutamate racemase in anti-caries drug design.